Permanent housing production process after 17 August 1999 Marmara Earthquake in Turkey - Tas, Nilufer; Cosgun, Nilay (International Journal of Strategic Property Management, 2011)
In recent years, one of the biggest investments and projects that developed in Turkey is in permanent housing. The emergency case experienced after the 17 August 1999 Marmara Earthquake featured the permanent housing need; thus, within the meaning of Disaster Law, a large number of housings were to be built in designated residential areas in various provinces. Once a building has been designed, impediments that arise either cannot be fixed any longer or require an extra cost to be fixed. In order to create a high quality built environment, production process of constructions as a long lasting effect becomes important. This study examines how the production process of the permanent housings to be built in Turkey after 1999 Marmara Earthquake was managed considering the current legal framework. In this context, the aim is to state how permanent housings are produced and determination of the points seen as problems by the builders (contractors) and occupants through this process. The main concern is to determine the outcomes that could act as answer to problems that might arise in permanent housing production after a probable earthquake. The obtained information is thought to act as reference in the practices of meeting permanent housing need that will arise after disasters.First Publish Online: 5 Oct 2011